Production method for preparing autoclaved aerated concrete from solid waste tail gas powder

By screening solid waste exhaust powder, removing impurities, controlling humidity, uniformizing particle size and optimizing ingredients, the utilization problem of solid waste exhaust powder in concrete production is solved, the quality and performance of concrete is improved, production costs are reduced, and the sustainable utilization of resources is achieved.

CN119613000APending Publication Date: 2025-03-14HENAN BUILDING MATERIALS RES & DESIGN LNSTITUTE CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510023560.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing concrete production technology cannot effectively utilize solid waste exhaust powder, resulting in increased difficulty and cost of solid waste treatment, and is highly dependent on natural resources, affecting sustainable development.

Method used

By screening out large particles of impurities in solid waste exhaust powder and removing iron filings, plastics and wood chips, humidity detection and evaluation, screening and drying, grinding and screening to obtain solid waste exhaust powder with uniform particle size, and mixing it with siliceous material, calcium material and aerator, orthogonal tests are designed to optimize the ratio.

Benefits of technology

The purification and resource utilization of solid waste exhaust powder has been achieved, the quality and performance of autoclaved aerated concrete has been improved, production costs have been reduced, and the requirements of sustainable development have been met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613000A_ABST
    Figure CN119613000A_ABST
Patent Text Reader

Abstract

The invention discloses a production method for preparing autoclaved aerated concrete from solid waste tail gas powder, and relates to the technical field of concrete production.The production method of the autoclaved aerated concrete comprises the following steps that S1, large-particle impurities in the solid waste tail gas powder are screened out; s2, scrap iron, plastic and wood chips are removed; s3, humidity detection and evaluation are carried out; s4, screening treatment is conducted, and drying is conducted; s5, the dried solid waste tail gas powder is screened, ground and screened; s6, measuring the chemical composition of the solid waste tail gas powder; s7, adding an air entraining agent into the solid waste tail gas powder, the siliceous material and the calcareous material; s8, designing a three-factor three-level orthogonal test; and S9, post-treatment is carried out. According to the method, large-particle impurities in the solid waste tail gas powder are screened out, scrap iron, plastic and wood chips in the solid waste tail gas powder are removed, the solid waste tail gas powder can be purified, resource recycling is achieved, the quality of the autoclaved aerated concrete is improved, and the production cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete production, and in particular to a production method for preparing autoclaved aerated concrete with solid waste tail gas powder. Background Art

[0002] Traditional concrete production cannot utilize solid waste tail gas powder, which increases the difficulty and cost of solid waste treatment. It mainly relies on natural sand and gravel aggregates and cement materials, and has a low utilization rate of renewable or recycled materials, resulting in over-exploitation and waste of natural resources, which is not conducive to sustainable development. The concrete production of this application can purify and utilize solid waste tail gas powder, reduce solid waste emissions, reduce dependence on natural resources, and at the same time improve the quality of autoclaved aerated concrete and reduce production costs.

[0003] The defects of existing concrete production are:

[0004] 1. Patent document CN110803911B discloses an autoclaved aerated concrete board and a preparation method thereof. The document mainly considers how to improve the sound insulation capacity of the autoclaved aerated concrete board, but does not consider how to solve the problems of solid waste tail gas powder raw material purification, resource recycling, improving the quality of autoclaved aerated concrete and reducing production costs;

[0005] 2. Patent document CN103626464B discloses a production process for autoclaved aerated concrete blocks. The document mainly considers how to reduce the weight of autoclaved aerated concrete blocks and improve the thermal insulation performance, but does not consider how to solve the problems of solid waste tail gas powder humidity control, particle size uniformity, drying efficiency and effect, improving the performance of autoclaved aerated concrete and optimizing the production process;

[0006] 3. Patent document CN107162513B discloses a method for preparing autoclaved aerated concrete blocks. The document mainly considers how to improve the compressive strength of autoclaved aerated concrete blocks, but does not consider how to solve the problems of uneven raw material particle size, low utilization rate and difficulty in ensuring the quality of autoclaved aerated concrete;

[0007] 4. Patent document CN112976279B discloses a method for processing autoclaved aerated concrete building materials. The document mainly considers how to solve the problem of uniform distribution of bubbles in the aerated concrete raw materials after entering the square frame mold, but does not consider how to optimize the performance of autoclaved aerated concrete, improve environmental benefits, and improve the material compatibility between siliceous materials, calcareous materials and solid waste tail gas powder. Summary of the invention

[0008] The object of the present invention is to provide a method for preparing autoclaved aerated concrete from solid waste tail gas powder, so as to solve the problems raised in the above background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: a method for preparing autoclaved aerated concrete from solid waste tail gas powder, the method for producing autoclaved aerated concrete is as follows:

[0010] S1. Screen out large particles of impurities in solid waste tail gas powder;

[0011] S2, remove iron filings, plastics and wood chips from solid waste tail gas powder;

[0012] S3. Detect and evaluate the humidity of solid waste tail gas powder;

[0013] S4, screening the solid waste tail gas powder and drying them separately;

[0014] S5, screening the dried solid waste tail gas powder, and grinding and screening to obtain solid waste tail gas powder with an average particle size of less than 1 mm;

[0015] S6. Determine the chemical composition of the solid waste tail gas powder by X-ray fluorescence spectrometer;

[0016] S7, mixing solid waste tail gas powder, siliceous material and calcareous material, and adding an air entraining agent;

[0017] S8. Design an orthogonal experiment with three factors and three levels;

[0018] S9, batching, pouring, gasification, cutting and autoclaving and curing the produced autoclaved aerated concrete blocks;

[0019] S10. Conduct dry density and compressive strength tests, drying shrinkage value tests, frost resistance tests and thermal conductivity tests on autoclaved aerated concrete;

[0020] In S1, the following is also included:

[0021] S11, sending the solid waste tail gas powder to the sorting screen, the screen mesh aperture is 25mm, large particles of impurities cannot pass through the screen and are retained on the screen surface, and the solid waste tail gas powder with an average particle size of less than 25mm is obtained;

[0022] In S2, it also includes the following:

[0023] S21. First, the solid waste tail gas powder is sent to the magnetic separator. The iron filings are adsorbed on the surface of the magnetic drum of the magnetic separator and automatically fall off as it rotates to the non-magnetic area. The solid waste tail gas powder continues to be transported without being affected by the magnetic field. The adsorbed iron filings and the non-adsorbed solid waste tail gas powder are collected at the discharge port of the magnetic separator. Then the solid waste tail gas powder is sent to the density separator. The plastic is sorted to the upper low-density area, and the solid waste tail gas powder remains in the lower high-density area. The plastic and solid waste tail gas powder are collected at the discharge port of the separator. Finally, the solid waste tail gas powder is sent to the air separation equipment. The lighter wood chips are carried away by the airflow due to their low density and light weight and enter the collection device above. The heavier solid waste tail gas powder falls due to gravity and enters the collection device below to obtain the solid waste tail gas powder after removing the iron filings, plastics and wood chips.

[0024] Preferably, S3 further includes the following:

[0025] S31. Use an infrared moisture meter to detect the humidity of the solid waste tail gas powder from which iron filings, plastics and wood chips have been removed, and compare the measured humidity value with the set humidity of 30%. If the humidity value is greater than 30%, drying treatment is required. If the humidity value is less than or equal to 30%, subsequent treatment is carried out directly.

[0026] Preferably, in S4, the following is also included:

[0027] S41, sending the solid waste tail gas powder into a vibrating screen for screening, the aperture of the screen is 5 mm, and the screen is screened to obtain the solid waste tail gas powder on the screen with a diameter greater than 5 mm and the solid waste tail gas powder under the screen with a diameter less than 5 mm;

[0028] S42. Use a hot air dryer to dry the solid waste tail gas powder on the sieve and the solid waste tail gas powder under the sieve respectively, set the drying temperature to 150°C and 80°C, and the time to 7h and 4h. After drying, take the solid waste tail gas powder out of the hot air dryer and cool it to room temperature.

[0029] Preferably, in S5, the following is also included:

[0030] S51, sending the dried solid waste tail gas powder on the sieve and the solid waste tail gas powder under the sieve into a vibrating screen for screening, the aperture of the sieve is 1 mm, and obtaining solid waste tail gas powder with an average particle size of less than 1 mm and solid waste tail gas powder with an average particle size of more than 1 mm;

[0031] S52. Use a vibration mill to grind solid waste tail gas powder with an average particle size greater than 1 mm. The ground solid waste tail gas powder is sent to a vibration screen for screening again. The aperture of the screen is 1 mm, and the solid waste tail gas powder that does not meet the average particle size of less than 1 mm is removed.

[0032] Preferably, during the grinding process of solid waste tail gas powder with an average particle size greater than 1 mm, sampling is performed every 0.5 h to detect the particle size distribution of the solid waste tail gas powder, and the grinding is stopped when the average particle size is less than 1 mm.

[0033] Preferably, in S7, the following is also included:

[0034] S71. The siliceous materials include quartz sand and shale, and the calcareous materials include cement and desulfurized gypsum. The siliceous materials are ground with a vibration mill and sieved to obtain quartz sand with an average particle size of 1 mm and shale with an average particle size of 3 mm.

[0035] S72, firstly, dry mixing is performed, and siliceous materials are added to a continuous mixer, and the ratio of quartz sand to shale is 1:1, and then calcium materials and solid waste tail gas powder are added. During the dry mixing process, the speed of the continuous mixer is 20r / min, and the mixing time is 10min;

[0036] S73. After dry mixing is completed, pure water dissolved with triisopropanolamine is added for wet mixing. During the wet mixing process, the speed of the continuous mixer is 30r / min, and the mixing time is 10min. After stirring evenly, an aerating agent is added, and the aerating agent is aluminum powder, and stirred evenly again.

[0037] Preferably, in S8, the following is also included:

[0038] S81. Under the condition that the addition amount of triethanolamine is 0.05% of the cement content, three conditions of siliceous material, cement and desulfurized gypsum are selected, and a three-factor three-level orthogonal experiment is designed. The siliceous material accounts for 6%, 9% and 12% respectively, the cement accounts for 7%, 10% and 13% respectively, the desulfurized gypsum accounts for 1%, 2% and 3% respectively, and the remainder is solid waste tail gas powder. The water-cement ratio is 0.4.

[0039] Preferably, in S9, the following is also included:

[0040] S91, pouring the mixed materials into a mold of 600mm×200mm×250mm for casting;

[0041] S92, placing the cast autoclaved aerated concrete block into an autoclave for autoclave curing, raising the temperature in the autoclave to 160° C. at a rate of 5° C. / min, and the pressure to 1.5 MPa, maintaining constant temperature and pressure curing for 2 hours, lowering the temperature and pressure in the autoclave to room temperature, and taking out the autoclaved aerated concrete block;

[0042] S93. In an environment with a temperature of 18°C ​​and a humidity of 60%, water-soaked gunny bags are used to cover the surface of the autoclaved aerated concrete blocks, and the autoclaved aerated concrete blocks are naturally cured. After the curing, the molding moisture content of the autoclaved aerated concrete blocks is 14%.

[0043] Preferably, in S10, the following is also included:

[0044] S101, dry density and compressive strength test, drying shrinkage value test and frost resistance test shall be carried out in accordance with the provisions of GB / T11969.

[0045] Preferably, in S10, the following is also included:

[0046] S102. Thermal conductivity test shall be carried out in accordance with the provisions of GB / T10294.

[0047] Compared with the prior art, the present invention has the following beneficial effects:

[0048] 1. The present invention removes large-particle impurities in solid waste tail gas powder and removes iron filings, plastics and sawdust in the solid waste tail gas powder. The solid waste tail gas powder contains large-particle impurities, iron filings, plastics and sawdust, which are not conducive to the preparation of autoclaved aerated concrete. These impurities not only affect the physical and mechanical properties of autoclaved aerated concrete, but also damage the production equipment. Through screening, magnetic separation, density separation and air separation steps, these impurities can be effectively removed, the purity of solid waste tail gas powder can be improved, and reliable raw materials can be provided for the subsequent preparation of high-quality autoclaved aerated concrete. As an industrial waste, solid waste tail gas powder will pollute the environment if it is directly discharged or improperly handled, and converting it into autoclaved aerated concrete The raw materials of soil not only realize the resource utilization of waste, but also reduce the exploitation of natural resources, which is in line with the concept of sustainable development. The solid waste tail gas powder that has been purified has a more uniform composition and a low impurity content, which is conducive to the preparation of autoclaved aerated concrete with stable performance and reliable quality. This autoclaved aerated concrete has the advantages of light weight, high strength, thermal insulation and heat insulation, and has broad application prospects in the field of construction. At the same time, using solid waste tail gas powder as raw material to prepare autoclaved aerated concrete can reduce dependence on traditional raw materials, thereby reducing production costs to a certain extent. Therefore, it can solve the problems of solid waste tail gas powder raw material purification, resource recycling, improving the quality of autoclaved aerated concrete and reducing production costs.

[0049] 2. The present invention detects and evaluates the humidity of solid waste tail gas powder, then screens and dries the solid waste tail gas powder. The humidity of the solid waste tail gas powder has an important influence on its subsequent processing and the quality of the final autoclaved aerated concrete. Excessive humidity makes it difficult to control moisture during the preparation of autoclaved aerated concrete, affecting the strength and stability of the autoclaved aerated concrete. By detecting and evaluating the humidity and performing necessary drying treatment according to the detection results, it can be ensured that the humidity of the solid waste tail gas powder is within a suitable range, providing stable raw material conditions for subsequent processing. Screening treatment is a key step to ensure the uniformity of the particle size of the solid waste tail gas powder. The solid waste tail gas powder is divided into two parts, the upper part and the lower part, by a vibrating screen. For solid waste tail gas powders of different particle sizes, different drying temperatures and times are used to more effectively remove moisture. At the same time, avoid changes in material properties caused by excessive drying. The use of hot air dryers, combined with appropriate drying temperature and time settings, can ensure that the solid waste exhaust powder reaches an ideal humidity level during the drying process while maintaining its original physical and chemical properties. The organic combination of humidity control, screening treatment and drying steps can significantly improve the quality of solid waste exhaust powder, thereby improving the overall performance of autoclaved aerated concrete. By introducing humidity detection and evaluation links, the production process is made more scientific and refined. Targeted treatment based on the actual situation of solid waste exhaust powder can reduce unnecessary waste and losses, improve production efficiency and economic benefits, and therefore solve the problems of humidity control, particle size uniformity, drying efficiency and effect of solid waste exhaust powder, improve the performance of autoclaved aerated concrete and optimize the production process.

[0050] 3. The present invention obtains solid waste tail gas powder with an average particle size of less than 1 mm by screening the dried solid waste tail gas powder, and grinding and screening it. The dried solid waste tail gas powder is divided into two parts with an average particle size of less than 1 mm and greater than 1 mm by a vibrating screen, and the part greater than 1 mm is ground until its average particle size is also less than 1 mm, which can ensure that the solid waste tail gas powder finally used to prepare autoclaved aerated concrete has a uniform particle size distribution. This particle size control helps to improve the density and strength of autoclaved aerated concrete, while improving its working performance and durability. Through the grinding process, the solid waste tail gas powder with a larger particle size is refined, thereby improving its utilization rate as a raw material for autoclaved aerated concrete, helping to reduce the waste of raw materials, reducing production costs, and meeting It conforms to the principles of resource conservation and recycling. At the same time, solid waste tail gas powder with uniform particle size helps to form a more uniform pore structure when preparing autoclaved aerated concrete, thereby improving the thermal insulation and mechanical properties of autoclaved aerated concrete. In addition, uniform particle size distribution also helps to reduce the shrinkage and cracking of autoclaved aerated concrete during the hardening process and improve the overall quality of the product. During the grinding process, regular sampling and testing of the particle size distribution of solid waste tail gas powder are carried out, and the grinding time and intensity are adjusted according to the test results to ensure that the grinding effect reaches the best state. This production process optimization method based on real-time feedback helps to improve production efficiency and product quality stability, and therefore can solve the problems of uneven raw material particle size, low utilization rate and difficult to ensure the quality of autoclaved aerated concrete.

[0051] 4. The present invention designs a three-factor three-level orthogonal experiment. Under the condition that the addition amount of triethanolamine is 0.05% of the cement content, three conditions of siliceous material, cement and desulfurized gypsum are selected to design a three-factor three-level orthogonal experiment. The siliceous material accounts for 6%, 9% and 12% respectively, the cement accounts for 7%, 10% and 13% respectively, the desulfurized gypsum accounts for 1%, 2% and 3% respectively, and the remainder is solid waste tail gas powder. Through the orthogonal experiment, the optimal proportion range of siliceous material, cement and desulfurized gypsum, as well as the best combination thereof, can be determined, so as to prepare autoclaved aerated concrete with better performance, higher strength, better durability and lower permeability. At the same time, By adjusting the proportion of different materials, the production cost can be effectively reduced while ensuring performance. By appropriately increasing the proportion of solid waste exhaust powder and maintaining or improving the overall performance of the material, the resource utilization of waste can be realized and the dependence on new materials can be reduced. The effective utilization of desulfurized gypsum as an industrial waste not only reduces environmental pollution, but also realizes the recycling of resources. At the same time, the addition of solid waste exhaust powder further promotes the resource utilization of waste, helps to reduce environmental pollution and improve the environmental benefits of the project. Therefore, it can solve the problems of optimizing the performance of autoclaved aerated concrete, improving environmental benefits and improving the material compatibility between siliceous materials, calcium materials and solid waste exhaust powder. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a production flow chart of the present invention. DETAILED DESCRIPTION

[0053] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0054] Embodiment 1,

[0055] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0056] S1. Screen out large particles of impurities in solid waste tail gas powder;

[0057] In S1, the following are also included:

[0058] S11. Send the solid waste tail gas powder into the sorting screen with a mesh size of 25 mm. Large particles of impurities cannot pass through the screen and are retained on the screen surface, thereby obtaining solid waste tail gas powder with an average particle size of less than 25 mm.

[0059] Furthermore, the sorting screen has a sieve with a specific aperture of 25mm, which is used to separate solid waste exhaust gas powder of different particle sizes. The sieve with an aperture of 25mm can ensure that most of the large particle impurities are effectively retained. During the screening process, particles larger than 25mm cannot pass through the sieve and are retained on the sieve surface. Solid waste exhaust gas powder with smaller particle sizes passes through the sieve and falls into the collection device below. The particle size of solid waste exhaust gas powder passing through the sieve is small, which meets the subsequent production requirements.

[0060] After the screening process, the solid waste exhaust powder obtained has removed most of the large particle impurities, including but not limited to stones, metal fragments, dead grass and branches, and the particle size distribution is more uniform, providing high-quality raw materials for the subsequent preparation of autoclaved aerated concrete.

[0061] Embodiment 2:

[0062] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0063] S2, remove iron filings, plastics and wood chips from solid waste tail gas powder;

[0064] In S2, it also includes the following:

[0065] S21. First, the solid waste tail gas powder is sent to the magnetic separator. The iron filings are adsorbed on the surface of the magnetic drum of the magnetic separator and automatically fall off as it rotates to the non-magnetic area. The solid waste tail gas powder continues to be transported without being affected by the magnetic field. The adsorbed iron filings and the non-adsorbed solid waste tail gas powder are collected at the discharge port of the magnetic separator. Then the solid waste tail gas powder is sent to the density separator. The plastic is sorted to the upper low-density area, and the solid waste tail gas powder remains in the lower high-density area. The plastic and solid waste tail gas powder are collected at the discharge port of the separator. Finally, the solid waste tail gas powder is sent to the air separation equipment. The lighter wood chips are carried away by the airflow due to their low density and light weight and enter the collection device above. The heavier solid waste tail gas powder falls due to gravity and enters the collection device below to obtain the solid waste tail gas powder after removing the iron filings, plastics and wood chips.

[0066] Furthermore, the strong magnetic field generated by the magnetic drum is used to separate magnetic iron filings from the solid waste tail gas powder, and the solid waste tail gas powder is fed into the feed port of the magnetic separator. The iron filings are adsorbed on the surface of the magnetic drum under the action of the magnetic field, and automatically fall off after rotating to the non-magnetic area. At the same time, the solid waste tail gas powder not affected by the magnetic field continues to be transported to the discharge port, and the adsorbed iron filings and the unadsorbed solid waste tail gas powder are collected at the discharge port of the magnetic separator.

[0067] Plastics and solid waste tail gas powder are separated by using the difference in density. The solid waste tail gas powder after magnetic separation is sent to the feed port of the density separator. Plastics float in the upper low-density area due to their low density, while solid waste tail gas powder remains in the lower high-density area. Two sets of collection devices are set at the discharge port of the separator to collect plastics and solid waste tail gas powder respectively.

[0068] By utilizing the force of airflow on the material, wood chips with low density and light weight are separated from the solid waste exhaust gas powder, and the solid waste exhaust gas powder that has been density-sorted is sent to the feed port of the air separation equipment. The wood chips are carried away by the airflow due to their low density and light weight and enter the collecting device above, while the heavier solid waste exhaust gas powder falls due to gravity and enters the collecting device below, thereby obtaining the solid waste exhaust gas powder after removing iron filings, plastics and wood chips. The solid waste exhaust gas powder is purer and suitable for subsequent autoclaved aerated concrete production.

[0069] Embodiment 3,

[0070] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0071] S3. Detect and evaluate the humidity of solid waste tail gas powder;

[0072] In S3, it also includes the following:

[0073] S31. Use an infrared moisture meter to detect the humidity of the solid waste tail gas powder from which iron filings, plastics and wood chips have been removed, and compare the measured humidity value with the set humidity of 30%. If the humidity value is greater than 30%, drying treatment is required. If the humidity value is less than or equal to 30%, subsequent treatment is carried out directly.

[0074] Furthermore, the infrared moisture meter probe is aimed at the solid waste tail gas powder sample from which iron filings, plastics and wood chips have been removed, and the instrument is started for measurement. The infrared moisture meter will calculate the humidity value based on the absorption or reflection characteristics of the solid waste tail gas powder to infrared light;

[0075] Set the humidity standard to 30%, and compare the measured humidity value with the set 30%. If the humidity value is greater than 30%, it means that the humidity of the solid waste exhaust gas powder is too high and needs to be dried to reduce its humidity. Excessive humidity will affect the strength and stability of autoclaved aerated concrete, and even cause blockage and bonding problems during the production process. If the humidity value is less than or equal to 30%, it means that the humidity of the solid waste exhaust gas powder is within the appropriate range and the subsequent production steps can be carried out directly.

[0076] Embodiment 4:

[0077] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0078] S4, screening the solid waste tail gas powder and drying them separately;

[0079] In S4, it also includes the following:

[0080] S41, sending the solid waste tail gas powder into a vibrating screen for screening, the aperture of the screen is 5 mm, and the screen is screened to obtain the solid waste tail gas powder on the screen with a diameter greater than 5 mm and the solid waste tail gas powder under the screen with a diameter less than 5 mm;

[0081] S42. Use a hot air dryer to dry the solid waste tail gas powder on the sieve and the solid waste tail gas powder under the sieve respectively, set the drying temperature to 150°C and 80°C, and the time to 7h and 4h. After drying, take the solid waste tail gas powder out of the hot air dryer and cool it to room temperature.

[0082] Further, a vibrating screen is used for screening. The vibrating screen can use vibration force to make the material jump and roll on the screen, thereby achieving effective screening. The aperture of the screen is set to 5 mm. After screening, solid waste tail gas powder with a diameter greater than 5 mm on the screen and solid waste tail gas powder with a diameter less than 5 mm under the screen are obtained;

[0083] Use a hot air dryer for drying. The hot air dryer can generate high-temperature hot air. Through the convection and conduction of the hot air, the moisture in the solid waste tail gas powder is evaporated. The solid waste tail gas powder on the sieve has a large particle size and the internal moisture evaporation rate is relatively slow. Therefore, the drying temperature is set to 150°C and the time is 7 hours to ensure that the solid waste tail gas powder is fully dried without being over-burned.

[0084] The solid waste exhaust powder under the sieve has a small particle size, a large specific surface area, and a fast evaporation rate of internal moisture. Therefore, the drying temperature is set to 80°C and the time is 4 hours to ensure that the solid waste exhaust powder is fully dried without excessive burning. After drying, the solid waste exhaust powder is removed from the hot air dryer and cooled to room temperature to prevent the solid waste exhaust powder from deteriorating or being damaged during subsequent processing or storage.

[0085] Embodiment 5,

[0086] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0087] S5, screening the dried solid waste tail gas powder, and grinding and screening to obtain solid waste tail gas powder with an average particle size of less than 1 mm;

[0088] In S5, it also includes the following:

[0089] S51, sending the dried solid waste tail gas powder on the sieve and the solid waste tail gas powder under the sieve into a vibrating screen for screening, the aperture of the sieve is 1 mm, and obtaining solid waste tail gas powder with an average particle size of less than 1 mm and solid waste tail gas powder with an average particle size of more than 1 mm;

[0090] S52. Use a vibration mill to grind solid waste tail gas powder with an average particle size greater than 1 mm. The ground solid waste tail gas powder is sent to a vibration screen for screening again. The aperture of the screen is 1 mm, and the solid waste tail gas powder that does not meet the average particle size of less than 1 mm is removed.

[0091] During the grinding process of solid waste exhaust gas powder with an average particle size greater than 1 mm, samples are taken every 0.5 hours to detect the particle size distribution of the solid waste exhaust gas powder, and the grinding is stopped until the average particle size is less than 1 mm.

[0092] Furthermore, the solid waste tail gas powder with an average particle size greater than 1 mm is sent to a vibration mill for grinding. The vibration mill refines the large particle size material through high-frequency vibration and grinding. During the grinding process, sampling is performed every 0.5 hours to detect the particle size distribution of the solid waste tail gas powder, which can ensure the grinding effect and avoid changes in material properties caused by excessive grinding.

[0093] When it is detected that the average particle size of the solid waste exhaust gas powder is less than 1mm, the grinding is stopped, and the ground solid waste exhaust gas powder is sent to the vibrating screen for screening again. The aperture of the screen is still 1mm to remove any larger particles that do not meet the requirements. The final result is solid waste exhaust gas powder with an average particle size of less than 1mm, which is used as a qualified raw material for the production of autoclaved aerated concrete.

[0094] Embodiment 6,

[0095] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0096] S6. Determine the chemical composition of solid waste tail gas powder by X-ray fluorescence spectrometer.

[0097] Furthermore, the chemical composition of solid waste tail gas powder is as follows:

[0098]

[0099]

[0100] The measurement results show that the chemical composition of solid waste tail gas powder is Si02>Ca0>Al203>Fe203>Fe0>MgO>TiO2>K20>Na2O>P205>SO3>ZnO>MnO>CuO>Cr304>Cr203.

[0101] Embodiment 7,

[0102] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0103] S7, mixing solid waste tail gas powder, siliceous material and calcareous material, and adding an air entraining agent;

[0104] In S7, it also includes the following:

[0105] S71. The siliceous materials include quartz sand and shale, and the calcareous materials include cement and desulfurized gypsum. The siliceous materials are ground with a vibration mill and sieved to obtain quartz sand with an average particle size of 1 mm and shale with an average particle size of 3 mm.

[0106] S72, firstly, dry mixing is performed, and siliceous materials are added to a continuous mixer, and the ratio of quartz sand to shale is 1:1, and then calcium materials and solid waste tail gas powder are added. During the dry mixing process, the speed of the continuous mixer is 20r / min, and the mixing time is 10min;

[0107] S73. After dry mixing is completed, pure water dissolved with triisopropanolamine is added for wet mixing. During the wet mixing process, the speed of the continuous mixer is 30r / min, and the mixing time is 10min. After stirring evenly, an aerating agent is added, and the aerating agent is aluminum powder, and stirred evenly again.

[0108] further,

[0109] Embodiment 8,

[0110] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0111] S8. Design an orthogonal experiment with three factors and three levels;

[0112] In S8, it also includes the following:

[0113] S81. Under the condition that the addition amount of triethanolamine is 0.05% of the cement content, three conditions of siliceous material, cement and desulfurized gypsum are selected, and a three-factor three-level orthogonal experiment is designed. The siliceous material accounts for 6%, 9% and 12% respectively, the cement accounts for 7%, 10% and 13% respectively, the desulfurized gypsum accounts for 1%, 2% and 3% respectively, and the remainder is solid waste tail gas powder. The water-cement ratio is 0.4.

[0114] Further, the orthogonal test ratio is as follows:

[0115]

[0116]

[0117] Through orthogonal experimental design, the addition amount of triethanolamine is fixed at 0.05% of the cement content. Three levels are set for siliceous materials, cement and desulfurized gypsum for testing. The proportions of siliceous materials are 6%, 9% and 12%, respectively, the proportions of cement are 7%, 10% and 13%, respectively, and the proportions of desulfurized gypsum are 1%, 2% and 3%, respectively. Since the total proportion of these materials cannot exceed 100%, the remaining percentage is the proportion of solid waste tail gas powder.

[0118] In each group of tests, except for the different proportions of siliceous materials, cement and desulfurized gypsum, other conditions should remain consistent to ensure the accuracy of the test results. By conducting orthogonal tests, the performance data of autoclaved aerated concrete in each group of tests can be collected, and then the test data can be processed and analyzed to determine the influence of each factor on the performance of concrete and the optimal ratio combination, which will help improve the quality and performance of autoclaved aerated concrete, reduce production costs, and promote the resource utilization of solid waste tail gas powder.

[0119] Embodiment 9,

[0120] See also Figure 1 The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0121] S9, batching, pouring, gasification, cutting and autoclaving and curing the produced autoclaved aerated concrete blocks;

[0122] In S9, it also includes the following:

[0123] S91, pouring the mixed materials into a mold of 600mm×200mm×250mm for casting;

[0124] S92, placing the cast autoclaved aerated concrete block into an autoclave for autoclave curing, raising the temperature in the autoclave to 160° C. at a rate of 5° C. / min, and the pressure to 1.5 MPa, maintaining constant temperature and pressure curing for 2 hours, lowering the temperature and pressure in the autoclave to room temperature, and taking out the autoclaved aerated concrete block;

[0125] S93. In an environment with a temperature of 18°C ​​and a humidity of 60%, water-soaked gunny bags are used to cover the surface of the autoclaved aerated concrete blocks, and the autoclaved aerated concrete blocks are naturally cured. After the curing, the molding moisture content of the autoclaved aerated concrete blocks is 14%.

[0126] Further, the mixed materials are poured into a 600mm×200mm×250mm mold for casting, ensuring the standard size and shape of the autoclaved aerated concrete. After casting, the autoclaved aerated concrete will begin to gas and expand. During this stage, it is necessary to keep still and avoid disturbance to ensure that the bubbles are evenly distributed and fully expanded.

[0127] After the autoclaved aerated concrete blocks reach a certain strength, they are cut and placed in an autoclave for curing by heating and pressurizing. The temperature is raised to 160°C at a rate of 5°C / min, and the pressure is maintained at 1.5MPa. The blocks are cured at a constant temperature and pressure for 2 hours. This process helps to accelerate the hydration reaction and improve the strength and durability of the product.

[0128] After the curing is completed, slowly lower the temperature and pressure in the autoclave to room temperature and normal pressure, take out the autoclaved aerated concrete blocks, and cover the surface of the autoclaved aerated concrete blocks with water-soaked sacks in a suitable environment with a temperature of 18°C ​​and a humidity of 60% for natural curing, which will help further consolidate the physical properties of the autoclaved aerated concrete and reduce the molding moisture to the target value of 14%.

[0129] Embodiment 10,

[0130] See also Figure 1The present invention provides an embodiment: a method for preparing autoclaved aerated concrete from solid waste tail gas powder. The method for producing autoclaved aerated concrete is as follows:

[0131] S10. Conduct dry density and compressive strength tests, drying shrinkage value tests, frost resistance tests and thermal conductivity tests on autoclaved aerated concrete;

[0132] In S10, the following is also included:

[0133] S101, dry density and compressive strength test, drying shrinkage value test and frost resistance test shall be carried out in accordance with the provisions of GB / T11969;

[0134] S102. Thermal conductivity test shall be carried out in accordance with the provisions of GB / T10294.

[0135] Further, the dry density and compressive strength test results of autoclaved aerated concrete blocks are as follows:

[0136]

[0137]

[0138] The test results of dry density and compressive strength show that: as can be seen from the table, the compressive strength of all orthogonal groups reached the A5.0 level, that is, the compressive strength was above 5.0MPa, and the dry density level was mainly between B05 and B07, of which most groups were at the B06 level. The autoclaved aerated concrete blocks of all test groups met or exceeded the expected standards in terms of dry density and compressive strength, showing good physical and mechanical properties. Among them, the compressive strength and average dry density of orthogonal group 4 were the highest, that is, the compressive strength and average dry density of the autoclaved aerated concrete prepared under the conditions of 9% siliceous material, 7% cement, 1% desulfurized gypsum, 82.95% solid waste tail gas powder and 00.05% triethanolamine were the highest.

[0139] The drying shrinkage test results of autoclaved aerated concrete blocks are as follows:

[0140]

[0141]

[0142] The drying shrinkage value test results show that the drying shrinkage values ​​of all orthogonal groups are no more than 0.50 mm / m, which meets the standard requirements, that is, the autoclaved aerated concrete blocks prepared in this application show good dimensional stability during the drying process, and the drying shrinkage value is within a reasonable range. Among them, the drying shrinkage value of orthogonal group 8 is 0.34 mm / m, which is the lowest among all groups. Therefore, the drying shrinkage value test results show that orthogonal group 8 is the best because it shows the best dimensional stability during the drying process and has the lowest drying shrinkage value. Although the drying shrinkage values ​​of other groups also meet the standard requirements, in comparison, the performance of orthogonal group 8 is superior.

[0143] The test results of frost resistance of autoclaved aerated concrete blocks are as follows:

[0144]

[0145]

[0146] The results of the frost resistance test show that the average post-freezing mass loss and the average post-freezing strength loss of all orthogonal groups meet the standard requirements, that is, the post-freezing mass loss is ≤5.0%, and the post-freezing strength loss is ≤20%. The autoclaved aerated concrete blocks prepared in this application have mass and strength losses within an acceptable range after being subjected to freeze-thaw cycles, showing good frost resistance. Among them, the average post-freezing mass loss of 1.8% and the average post-freezing strength loss of 6% of orthogonal group 4 are the lowest among all groups, showing the best frost resistance. Therefore, the results of the frost resistance test show that orthogonal group 4 is the best, and its mass and strength losses are the smallest after being subjected to freeze-thaw cycles.

[0147] The test results of thermal conductivity of autoclaved aerated concrete blocks are as follows:

[0148]

[0149] The test results of thermal conductivity coefficient show that the test values ​​of thermal conductivity coefficient of all orthogonal groups meet the standard limit requirements corresponding to their respective dry density levels, that is, the autoclaved aerated concrete blocks prepared in this application have a lower thermal conductivity coefficient, which is beneficial to building energy conservation and meets the requirements of thermal insulation materials. Among them, the dry density level of orthogonal group 2 is B05, and its corresponding standard limit value is ≤0.14W / (m·K), while the test value is 0.13W / (m·K), which is the lowest thermal conductivity value of all groups. Therefore, the test results of thermal conductivity coefficient show that orthogonal group 2 is the best because it has the lowest thermal conductivity coefficient at the same dry density level, and thus has the best thermal insulation performance;

[0150] Although the dry density level of orthogonal groups 4 and 8 is higher at B07, their thermal conductivity is also correspondingly higher. Although they still meet the standard requirements, their thermal insulation performance is not as good as the orthogonal groups with lower dry density levels and lower thermal conductivity.

[0151] In summary, orthogonal group 4 exhibits the highest compressive strength and average dry density, indicating that autoclaved aerated concrete has the best physical and mechanical properties under the conditions of 9% siliceous material, 7% cement, 1% desulfurized gypsum, 82.95% solid waste tail gas powder and 0.05% triethanolamine;

[0152] The drying shrinkage value of orthogonal group 8 is the lowest, which is 0.34mm / m, showing the best dimensional stability during the drying process. The average weight loss and average strength loss after freezing of orthogonal group 4 are the lowest among all groups, which are 1.8% and 6% respectively, showing the best anti-freezing performance. Orthogonal group 2 has the lowest thermal conductivity (0.13W / (m·K)) at the B05 dry density level, showing the best thermal insulation performance.

[0153] Although orthogonal group 4 performs well in compressive strength, average dry density and frost resistance, orthogonal group 8 is better in drying shrinkage value, which is crucial to ensure the dimensional stability of the material in long-term use. However, the advantage of orthogonal group 2 in thermal conductivity cannot be ignored for application scenarios that require good thermal insulation performance. From the perspective of comprehensive performance, orthogonal group 4 performs well in multiple key performance indicators, so it is a relatively balanced and excellent ratio scheme.

[0154] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing autoclaved aerated concrete from solid waste tail gas powder, characterized in that: The production method of autoclaved aerated concrete is as follows: S1. Screen out large particles of impurities in solid waste tail gas powder; S2, remove iron filings, plastics and wood chips from solid waste tail gas powder; S3. Detect and evaluate the humidity of solid waste tail gas powder; S4, screening the solid waste tail gas powder and drying them separately; S5, screening the dried solid waste tail gas powder, and grinding and screening to obtain solid waste tail gas powder with an average particle size of less than 1 mm; S6. Determine the chemical composition of the solid waste tail gas powder by X-ray fluorescence spectrometer; S7, mixing solid waste tail gas powder, siliceous material and calcareous material, and adding an air entraining agent; S8. Design an orthogonal experiment with three factors and three levels; S9, batching, pouring, gasification, cutting and autoclaving and curing the produced autoclaved aerated concrete blocks; S10. Conduct dry density and compressive strength tests, drying shrinkage value tests, frost resistance tests and thermal conductivity tests on autoclaved aerated concrete; In S1, the following is also included: S11, sending the solid waste tail gas powder to the sorting screen, the screen mesh diameter is 25mm, large particles of impurities cannot pass through the screen and are retained on the screen surface, and the solid waste tail gas powder with an average particle size of less than 25mm is obtained; In S2, it also includes the following: S21. First, the solid waste tail gas powder is sent to the magnetic separator. The iron filings are adsorbed on the surface of the magnetic drum of the magnetic separator and automatically fall off as it rotates to the non-magnetic area. The solid waste tail gas powder continues to be transported without being affected by the magnetic field. The adsorbed iron filings and the non-adsorbed solid waste tail gas powder are collected at the discharge port of the magnetic separator. Then the solid waste tail gas powder is sent to the density separator. The plastic is sorted to the upper low-density area, and the solid waste tail gas powder remains in the lower high-density area. The plastic and solid waste tail gas powder are collected at the discharge port of the separator. Finally, the solid waste tail gas powder is sent to the air separation equipment. The lighter wood chips are carried away by the airflow due to their low density and light weight and enter the collection device above. The heavier solid waste tail gas powder falls due to gravity and enters the collection device below to obtain the solid waste tail gas powder after removing the iron filings, plastics and wood chips.

2. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 1, characterized in that: In S3, it also includes the following: S31. Use an infrared moisture meter to detect the humidity of the solid waste tail gas powder from which iron filings, plastics and wood chips have been removed, and compare the measured humidity value with the set humidity of 30%. If the humidity value is greater than 30%, drying treatment is required. If the humidity value is less than or equal to 30%, subsequent treatment is carried out directly.

3. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 1, characterized in that: In S4, it also includes the following: S41, sending the solid waste tail gas powder into a vibrating screen for screening, the aperture of the screen is 5 mm, and the screen is screened to obtain the solid waste tail gas powder on the screen with a diameter greater than 5 mm and the solid waste tail gas powder under the screen with a diameter less than 5 mm; S42. Use a hot air dryer to dry the solid waste tail gas powder on the sieve and the solid waste tail gas powder under the sieve respectively, set the drying temperature to 150°C and 80°C, and the time to 7h and 4h. After drying, take the solid waste tail gas powder out of the hot air dryer and cool it to room temperature.

4. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 1, characterized in that: In S5, the following are also included: S51, sending the dried solid waste tail gas powder on the sieve and the solid waste tail gas powder under the sieve into a vibrating screen for screening, the aperture of the sieve is 1 mm, and obtaining solid waste tail gas powder with an average particle size of less than 1 mm and solid waste tail gas powder with an average particle size of more than 1 mm; S52. Use a vibration mill to grind solid waste tail gas powder with an average particle size greater than 1 mm. The ground solid waste tail gas powder is sent to a vibration screen for screening again. The aperture of the screen is 1 mm, and the solid waste tail gas powder that does not meet the average particle size of less than 1 mm is removed.

5. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 4, characterized in that: During the grinding process of solid waste exhaust gas powder with an average particle size greater than 1 mm, samples are taken every 0.5 hours to detect the particle size distribution of the solid waste exhaust gas powder, and the grinding is stopped until the average particle size is less than 1 mm.

6. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 1, characterized in that: In S7, it also includes the following: S71. The siliceous materials include quartz sand and shale, and the calcareous materials include cement and desulfurized gypsum. The siliceous materials are ground with a vibration mill and sieved to obtain quartz sand with an average particle size of 1 mm and shale with an average particle size of 3 mm. S72, firstly, dry mixing is performed, and siliceous materials are added to a continuous mixer, and the ratio of quartz sand to shale is 1:1, and then calcium materials and solid waste tail gas powder are added. During the dry mixing process, the speed of the continuous mixer is 20r / min, and the mixing time is 10min; S73. After dry mixing is completed, pure water dissolved with triisopropanolamine is added for wet mixing. During the wet mixing process, the speed of the continuous mixer is 30r / min, and the mixing time is 10min. After stirring evenly, an aerating agent is added, and the aerating agent is aluminum powder, and stirred evenly again.

7. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 1, characterized in that: In S8, it also includes the following: S81. Under the condition that the addition amount of triethanolamine is 0.05% of the cement content, three conditions of siliceous material, cement and desulfurized gypsum are selected, and a three-factor three-level orthogonal experiment is designed. The siliceous material accounts for 6%, 9% and 12% respectively, the cement accounts for 7%, 10% and 13% respectively, the desulfurized gypsum accounts for 1%, 2% and 3% respectively, and the remainder is solid waste tail gas powder. The water-cement ratio is 0.

4.

8. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 1, characterized in that: In S9, it also includes the following: S91, pouring the mixed materials into a mold of 600mm×200mm×250mm for casting; S92, placing the cast autoclaved aerated concrete block into an autoclave for autoclave curing, raising the temperature in the autoclave to 160° C. at a rate of 5° C. / min, and the pressure to 1.5 MPa, maintaining constant temperature and pressure curing for 2 hours, lowering the temperature and pressure in the autoclave to room temperature, and taking out the autoclaved aerated concrete block; S93. In an environment with a temperature of 18°C ​​and a humidity of 60%, water-soaked gunny bags are used to cover the surface of the autoclaved aerated concrete blocks, and the autoclaved aerated concrete blocks are naturally cured. After the curing, the molding moisture content of the autoclaved aerated concrete blocks is 14%.

9. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 1, characterized in that: In S10, the following is also included: S101, dry density and compressive strength test, drying shrinkage value test and frost resistance test shall be carried out in accordance with the provisions of GB / T11969.

10. The method for preparing autoclaved aerated concrete from solid waste tail gas powder according to claim 9, characterized in that: In S10, the following is also included: S102. Thermal conductivity test shall be carried out in accordance with the provisions of GB / T10294.

Citation Information

Patent Citations

  • A production process for autoclaved aerated concrete blocks

    CN103626464B

  • A method for preparing autoclaved aerated concrete blocks

    CN107162513B

  • Autoclaved aerated concrete (AAC) panels and their preparation methods

    CN110803911B

  • A method for processing autoclaved aerated concrete building materials

    CN112976279B